Simultaneous spectrophotometric determination of rare-earth and transition elements using partial least-squares (PLS) multivariate calibration - Camiña, José Manuel (2001)
A spectrophotometric method for the simultaneous determination of rare-earth and transition elements in synthetic superconductors, [(La1 – x Eu x )1.82Sr0.18CuO4], by the use of 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) as chelating agent was developed. The influence of chemical variables affecting the reaction was studied. A partial least-squares (PLS) multivariate calibration procedure was used to assess the data obtained from several calibration solutions measured over the wavelengths range 400–700 nm. The concentration range for Cu was (1–12) × 10–6 mol/L, while the range for the rare-earth elements La and Eu was (2–8) × 10–6 mol/L. The relative errors in the determinations were less than 5% in most cases.